The Relationship of Vitamin D3, D-Dimer, and Antinuclear Antibody Levels with Toxoplasmosis - Muna Jalal Aziz; Abeer Abbas Ali; Mohammed Fadhil Haddad; Basima Ahmed Abdullah (Medical Journal of Babylon)
Background:Toxoplasma gondii is an obligatory parasite that causes a zoonotic infection known as toxoplasmosis, which produces a wide range of clinical symptoms in humans and is considered the major cause of abortion in women. Immunocompromised patients are more likely to develop T. gondii infections due to parasite transmission over the placenta. Objective:The aim of this study was the determination of antinuclear antibody (ANA) and some biochemical parameters, such as vitamin D3 and D-dimer. Materials and Methods:This study was conducted in Kirkuk City extended from November 1, 2022 to March 21, 2023 included 200 blood samples from aborted women at Gynecological and Pediatric Hospital and Kirkuk General Hospital, Kirkuk, Iraq. The patient’s serum was assessed for ANAs, vitamin D3, and D-dimer. Results:Forty-seven percent of 200 women who had abortions tested positive for toxoplasmosis. Serum vitamin D3 levels were found to be substantially lower in Toxoplasma-positive cases than in Toxoplasma-negative cases, which was an unexpected finding. In addition, ANA results were statistically significant (P = 0.034). In our study, there was no discernible difference in the levels of D-dimer between the groups. Conclusion:This study investigated that there were significant differences in the level of vitamin D3 and the results of ANA between the groups in aborted women, whereas there were no obvious differences in D-dimer level between our study groups.